STRATEGI KELUARGA MISKIN MELANJUTKAN STUDI ANAKNYA KE PERGURUAN TINGGI (STUDI KASUS: KANAGARIAN TALU, KECAMATAN TALAMAU, KABUPATEN PASAMAN BARAT) - Sari, Cici Rahma; Elvawati, Elvawati; Anggreta, Dian Kurnia (Pendidikan Sosiologi, 2013)
Poverty is typically described as a lack of income to meet the basic needs of life. One way to get out of poverty is education. Poverty makes it difficult for people to get a better education. This is because the cost of education in general expensive. No all parents are able to finance their studies. But in Nagari Talu of 106 poor households, 15 % of parents send their children to college. The purpose of this study to describe the strategies of poor families in Nagari Talu continue their education in high to college. The theory used is instrumental social action proposed by Max Weber.This research method with qualitative approach and descriptive type. Selection of the study informants in doing proposive by sampling. How to collect data in this study is primary data and sedukner. Collection engineering data in this study is the observation, interviews, documentation. From the results of this study revealed that: strategies that parents use their children to continue their studies to college height: a) patterns of a double living, b) assistance from extended family, c) help fromn eighbors